Conflicts: A Game that Simulates Cognitive Dissonance in Decision Making - Yao, Morgan Spencer (Archīum Ateneo, 2021)
This research aims to develop a game that accurately simulates situations that would cause cognitive dissonance to the player. Cognitive dissonance is a psychological concept that involves situations of conflicting attitudes, beliefs, or behaviors that result in feelings of mental discomfort. The game is a visual novel with choice-based decisions that will influence the ending of the story. The player will have to make choices that will satisfy either their family for their happiness or their boss for money to spend on their family. In order to assess and measure the player’s cognitive dissonance, the investigators used a modified scale derived from Sweeney, Hausknecht, and Soutar’s research which uses three dimensions to measure dissonance after a major decision. The questions were in the form of a 7-point Likert scale and were integrated within the game itself and presented after the participant makes a major decision. The data was averaged for analysis. Results had shown that the game developed was only able to simulate average levels of cognitive dissonance.